The diversification and potential function of microbiome in sediment-water interface of methane seeps in South China Sea - Fu, Lulu; Liu, Yanjun; Wang, Minxiao; Lian, Chao; Cao, Lei; Wang, Weicheng; Sun, Yan; Wang, Nan; Li, Chaolun (Frontiers in Microbiology, 2024)
The sediment-water interfaces of cold seeps play important roles in nutrient transportation between seafloor and deep-water column. Microorganisms are the key actors of biogeochemical processes in this interface. However, the knowledge of the microbiome in this interface are limited. Here we studied the microbial diversity and potential metabolic functions at sedimentwater interface of two active cold seeps in the northern slope of South China Sea, Lingshui and Site F cold seeps. The microbial diversity and potential functions in the two cold seeps are obviously different. The microbial diversity of Lingshui interface areas, is found to be relatively low. Microbes associated with methane consumption are enriched in Lingshui samples, possibly due to the large and continuous eruptions of methane fluids. Methane consumption is mainly mediated by aerobic oxidation and denitrifying anaerobic methane oxidation (DAMO). The microbial diversity in Site F is higher than Lingshui. Fluids from seepage of Site F are mitigated by methanotrophic bacteria at the cyclical oxic-hypoxic fluctuating interface where intense redox cycling of carbon, sulfur, and nitrogen compounds occurs. The primary modes of microbial methane consumption are aerobic methane oxidation, along with DAMO, sulfatedependent anaerobic methane oxidation (SAMO). To sum up, anaerobic oxidation of methane (AOM) may be underestimated in cold seep interface microenvironments. Our findings highlight the significance of AOM and interdependence between microorganisms and their environments in the interface microenvironments, providing insights into the biogeochemical processes that govern these unique ecological systems.